Role of Seed-Zinc Content on Seed Longevity of Paddy Genotypes - JB MARUTHI,; SN VASUDEVAN,; BS JANAGOUDAR,; MOHAMMAD IBRAHIM,; SHIVANAGOUDA R DODDAGOUDAR,; B KISAN,; SANGEETA I MACHA, (Seed Research, 2026)
Ten paddy genotypes were selected to establish the role of seed-Zn content in maintaining seed longevity of paddy genotypes. The present study revealed clear genotypic variability with respect to storability among different paddy genotypes. The genotype with highest seed-Zn content (24.79 ppm) proved as good storer by recording highest seed quality parameters viz., seed germination (85.70%), seedling length (21.88 cm), seedling vigour index (1795), speed of germination (18.80), dehydrogenase enzyme activity (0.39 OD value), ±-amylase activity (12.47 mm) with lowest electrical conductivity (153.40 µS/cm) and moisture content (10.62%) at the end of twelve months of storage period. However, genotypes with low seed-Zn content showed lowest observations of various seed quality parameters.